Social interaction and family stability in basic education students - Cárdenas Loor, Alexandra (2022)
The incidence of family cohesion in social interaction and personality traits (locus of control) was studied in students of a basic education school in the Quevedo canton, Los Ríos province, Ecuador. A population of 190 individuals was considered, divided into 90 students (47%), 90 parents (guardians) of the family (47%), and 10 teachers (6%), to whom a two-question survey was applied, whose possible answers were: “agree”, “maybe”, and “disagree”. 48% of the students considered that interpersonal relationships influence the development of their personality and interpersonal relationships, while 53% indicated that they were capable and prepared to defend their personal interests. As for the representatives, 57% considered that interfamily communication facilitates interpersonal relationships optimally, and 34% considered that their representatives feel that the events of their lives are determined by the people who have authority over them. 40% of the teachers maintained that the personal actions of the students determine their present and future, while 60% share the idea that the number of friends a student "maybe" has is determined by their friendliness. Children and adolescents must consider that the actions of a person will always have consequences, so they must be the ones who make the most appropriate decisions, based on prior guidance from their parents or guardians.